2012
DOI: 10.1063/1.4737652
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a white noise at channel inlet on the parallel and wavy convective instabilities of Poiseuille-Rayleigh-Bénard flows

Abstract: Nicolas, Zoueidi, and Xin Phys. Fluids 24, 084101 (2012) used to make thin coatings on heated substrates from gaseous components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…A few examples, established experimentally, theoretically and numerically, for different Prandtl numbers and aspect ratios, can be found in [6][7][8][9] in the case of pure fluids. In the case of air PRB flows (Pr=0.7), a complete stability diagram at B≥10 is presented in [10]. It is partially reproduced in Fig.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…A few examples, established experimentally, theoretically and numerically, for different Prandtl numbers and aspect ratios, can be found in [6][7][8][9] in the case of pure fluids. In the case of air PRB flows (Pr=0.7), a complete stability diagram at B≥10 is presented in [10]. It is partially reproduced in Fig.…”
Section: Introductionmentioning
confidence: 71%
“…1). This instability is observed for sufficiently high Reynolds numbers (typically for Re>O (10) in air) and for Rayleigh numbers above a critical value varying between 1708 and 2000 when B>2 [9]. Carrière and Monkewitz (1999) [16] showed that this pattern is a convective instability of the basic conductive Poiseuille flow.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations